إلحاق ولد المغتصبة غير المتزوجة بالمغتصب في الفقه الإسلامي - سهيل, الأحمد (مجلة الإجتهاد القضائي, 2020)
تناولت هذه الدراسة إلحاق ولد المغتصبة غير المتزوجة بالمغتصب في الفقه الإسلامي، هادفة إلى إظهار وتجلية حكم الشرع فيها، فتبين أن الإسلام اهتم بالنسب وحرص على رعايته فعده واحدًا من الضرورات الخمس التي لا تستقيم حياة الناس إلا بحفظها، وبأن نشر الفضائل ومنع الرذائل هو من مباديء الإسلام السامية، وقد بحث الدراسة مسألة إلحاق المولود حال اغتصاب المرأة غير المتزوجة بالرجل الذي اغتصبها من وجهة نظر الفقه الإسلامي، حيث ظهر بعد بيان آراء العلماء وأدلتهم في حكمها بأنهم قد اختلفوا في إلحاقه بين الحظر والإباحة، وقد رجح الباحث رأي المجيزين بشروط وضوابط معتبرة. الكلمات المفتاحية: الاغتصاب، الزواج، النسب. Abstract : This study investigated the legality of the filiation, born out of wedlock, in Islamic jurisprudence. It aimed at showing as well revealing the Shara’s judgment in such a problem. It transpired that Islam is very interested in and keen to parenthood and kinship which were considered as one of the five necessities indispensable for the lives of people and that should be saved. The dissemination of virtues and prevention of vices are also among the high principles of Islam. However, this area of interest has been discussed. By reviewing the views of scientists’ investigatory procedures and its judgment, it has been found that they had fall into disputations in the horseshoe  between the ban and license. The researcher has agreed with the group who has admitted such a kinship under certain but regard conditions. Keywords: Rape, marriage, descent